18F-FDG PET/CT in Bladder Cancer. (December 2016) - Tagliabue, Luca; Russo, Giovanna; Lucignani, Giovanni
Abstract : Abstract: Urinary clearance of 18 F-FDG and variability in bladder wall FDG uptake may hamper the interpretation and limit the use of FDG-PET/CT for imaging bladder tumors. Nevertheless, careful combined evaluation of both CT and FDG-PET images of the urinary tract can provide useful findings. We present 2 cases of bladder cancer detected by FDG-PET/CT. These cases suggest that FDG uptake can be indicative of malignancy in bladder cancer when viewed in conjunction with CT scans and that whole-body FDG-PET/CT scans should always be reviewed with particular attention to the urinary tract because abnormalities suggestive of bladder cancer can be found unexpectedly.